About some myths, inaccuracies and controversies concerning the Turkish expedition to Vienna (1683) - Wybranowski, Dariusz (Balcanica Posnaniensia. Acta et studia, 2014)
In the article, the author has analyzed some myths, controversies and inaccuracies concerning the genesis, course and results of the armed expedition by Grand Vizier Kara Mustapha Pasha against Vienna in 1683. Some of them came into existence almost immediately after the victory at Vienna John III Sobieski, others were created or retained for various reasons later, especially in the Polish literature of the subject. One of the main purposes of the article is also the analysis of the media and film image of the Battle of Vienna. The article is an attempt to answer some research questions and some hypotheses on the basis of such written sources as the Turkish chronicles and the available literature of the subject.